The development of an assessment of freedom for people living with dementia - Brewin, C. (2021)
Within the UK over 850,000 people live with dementia, 650,000 remain in their homes with the support of 600,000 carers. A problem faced by community dwelling PLWD is that of becoming lost when leaving their home. Carers may restrict the freedom of PLWD due to concerns about their safety. Leaving the home unsafely is a significant risk for PLWD with up to a third of people living with the condition becoming lost at some point. This is a frightening and distressing experience which may lead to injury and anxiety. However, when involved in research people living with dementia have identified the benefits of being involved with their local community and environment. For those whose condition is more advanced being able to walk may be calming and reduce agitation and distress. The issue of freedom for people living with the dementia is then a difficult balance between the benefits of risk and safety. This research developed an assessment of freedom for people living with dementia and a theoretical model of freedom. The acronym FREEDEM was used for the assessment.